(untitled) (Research, Society and Development, 2021)
Objective: This study aimed to describe the factors that contribute to early weaning. Methods: this is an integrative review. Searches were conducted in Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrievel System Online (MEDLINE) and in the Nursing Database (BDENF), with search strategies that combined the keywords: maternal breastfeeding, weaning, postpartum period and prenatal care. Nine articles made up the final sample. Results: The perception of insufficient/weak milk was the most frequent reason, being mentioned in 66.66% of publications, followed by 33.33% of breast complications and 33.33% of incorrect breastfeeding latch. Conclusion: The identification of these factors that lead to early weaning is essential to promote more effective interventions in order to minimize the obstacles that lead to early weaning. It is essential that health professionals and managers can discuss these factors in a broader way and outline strategies favorable to improving adherence to AME.